Honeybee Flora at Kabre, Dolakha District - Bista, Sanjaya; Shivakoti, Gopal P (Nepal Agriculture Research Journal, 2011)
Adequate knowledge about bee flora is the prerequisite to initiate bee keeping. A study was conducted at Kabre area of Dolakha district during 1997-1999 to identify existing bee flora and develop a floral calendar. Based on the interview with bee farmers and visual observations, 119 important plant species were recorded, out of which 47 species were found major sources for honeybees. Spring season (mid-March to mid-June) and autumn season (mid-Sept to Oct) were identified as honey flow periods having a number of floral plants such as Guizotia abyssinica, Fraxinus floribunda, Prunus cerasoides, Pyrus communis, Castanopsis indica, Brassica spp., Citrus spp., Berberis spp., Rubus spp., Rhododendron spp. and Trifolium spp. Winter season (mid- Nov to Feb) is the critical dearth period with a few flowering plants like Reinwardtia indica, Pogestemon glaber, Caesalpinia spp. and Eupatorium spp. Depending upon the climatic conditions, possibility of planting multipurpose plants has been discussed. Based on available flora, major characteristics of these plant species, utility status and flowering duration a bee floral calendar was developed for Kabre. To conserve these floras, attention must be made to maintain and multiply the existing flora. Key words: Apis cerana; Bee flora; Bee keeping; Dearth period; Honey flow DOI: http://dx.doi.org/10.3126/narj.v4i0.4859 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 18-25 Uploaded date: 8 June, 2011